TREATMENT OF RENAL ANEMIA: FROM BLOOD TRANSFUSIONS AND EXOGENOUS STIMULANTS OF ERYTHROPOIESISTO NEW PHYSIOLOGICAL APPROACHES - K. A. Aitbaev; I. T. Murkamilov; V. V. Fomin (Сеченовский вестник)
The review presents new pharmaceuticals for the treatment of anemia in chronic kidney disease that have been developed in recent years and are currently in the clinical testing phase. Mechanisms of action, as well as potential side effects are examined. Based on the analysis of data from preliminary clinical trials, it is concluded that the new pharmaceuticals are highly effective and well tolerated by patients, and in the coming years, could be included in the therapeutic arsenal for treatment of nephrogenic anemia.